Anti-Zionism Ergo Antisemitism, an Intellectual Inquisition or a Semantic Crisis? The Case of France - Neffati, Imen (Zygon, 2025)
This article explores different readings of antisemitism in French political discourses since 1967 and in light of the ongoing war in Gaza. Drawing on literature that explores modern manifestations and evolving definitions of antisemitism, it explores arguments made for and reservations against the putative equivalence between antisemitism and anti-Zionism. First, while also exploring shifts in French Jewish identity, especially in its relation to the state of Israel, the article critically engages with the recentering of 1967 and the Six-Day War in the recent historiography of antisemitism in France and brings forward questions of audience and historical responsibility. The second section questions the "new antisemitism" and its roots in French Jewish identity. The final section challenges definitions of anti-Zionism, highlights the danger of alienating French Muslims in the name of protecting French Jews, and explores the promise of a "principled" anti-Zionism.